Anticipatory Grief among Chinese Family Caregivers of Patients with Advanced Cancer: A Cross-Sectional Study - Wenhua Yu; Qian Lu; Yuhan Lu; Hong Yang; Lichuan Zhang; Renxiu Guo; Xiaoting Hou (Asia-Pacific Journal of Oncology Nursing, 2021)
Objective: The objective of this study was to explore the interrelationship between anticipatory grief (AG), caregiver burden, communication, preparation for death, and coping style. Methods: A convenience sample of 256 Chinese family caregivers of patients with advanced cancer were recruited from an academic cancer hospital between April 2018 and May 2019. This cross-sectional survey included the AG Scale, caregiver burden (Caregiver Reaction Assessment), communication (Caregivers' Communication with Patients about Illness and Death Scale), preparation for death, and coping style (Simplified Coping Style Questionnaire). Structural equation modeling tested the interrelation between them. Results: The final model fitted the data acceptably (χ2 = 25.79, degrees of freedom = 17, P = 0.08, root mean square error of approximation = 0.05, goodness-of-fit index [GFI] = 0.98, adjusted GFI [AGFI] = 0.95, parsimony GFI [PGFI] = 0.46, normed fit index = 0.94, comparative fit index = 0.98). Poor communication contributed to less preparation for death and caregiver burden, which further aggravate AG. Communication was positively associated with AG. In addition, communication and positive coping style interacted to further influence caregiver burden. Conclusions: Preliminary results supported the model and showed that poor communication, less preparation for death, and caregiver burden contributed to AG while positive coping alleviated AG. Findings suggest the need for further studies to explore effective intervention for communication, preparation for death, burden, and coping style of caregivers to ultimately alleviate AG.